Burna jesen olimpijske 1984. i sarajevska inicijativa Udruženja španskih boraca / The Turbulent Olympic Autumn of 1984 and the Sarajevo Initiative by the Association of Yugoslav Brigadistas - Sarač-Rujanac, Dženita (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This text is a revew of a book by Olga Manojlović Pintar, Poslednja bitka: Španski borci i jugoslovenska kriza osamdesetih, Belgrade, Institute for Recent Serbian History, 2019, 276.